Left Colic Angle Volvulus Pressing the Spleen: A Case Report from the Yopougon University Hospital (Abidjan, Ivory Coast) - Assohoun, Krahiboue Toussaint Hubert; Koffi, Gnangoran Marcellin; Dah, Gninkpa Fredi (European Scientific Journal, ESJ, 2026)
Colonic volvulus is the torsion of the colon around its mesentery, which generally occurs at the level of the sigmoid colon and the caecum in 60 to 75% and 25 to 40% of cases, respectively. In contrast, volvulus of the splenic flexure is rare, occurring in only 1% of cases. We report a rare case of volvulus of the splenic flexure of the colon involving the spleen. The patient was a 54-year-old man with chronic constipation who had undergone a laparotomy for acute intestinal obstruction 11 years prior. The examination revealed an obstructive syndrome. Further investigation revealed a volvulus of the left colic flexure involving the spleen in its torsion, with necrosis of the splenic flexure but no perforation. We performed a high segmental colectomy with splenic loop and splenopexy. Splenic angle volvulus is a rare cause of colonic obstruction, and its location around the spleen makes it exceptional. Hence the importance of our study to improve its management.